Implementation Principles of the Religious Component in the Russian Educational System: Approaches and Solutions - Ivanova, Tatyana N. (2020)
An active discussion of the questions of the advisability of forming new principles of national unity and creating an orderly harmonious world in the minds of people, strengthening the educational functions of the state, its concern for public morality do not primarily concern education, humanization of its content, and revision of the educational process. The formation and implementation of a state policy adequate to this problem must comply with the requirements of our time, create, on the one hand, conditions for ensuring the rights and freedoms of citizens, including the observance of the fundamental principles of religious freedom, and on the other, develop legislative norms that regulate these rights. A legal democratic state provides for the formation of public policy in accordance with the needs of society and taking into account public thought. The secular nature of public education is not an obstacle to the introduction of disciplines in the provision of religious knowledge in the educational process of schools, religious knowledge can and should be considered as an element of secular culture. Knowledge of religion should be carried out by secular teachers, be neutral in content and not be accompanied by religious rites. The problems of the formation of moral and spiritual values, the worldview of a person, the introduction of religious disciplines in secondary schools are vividly discussed in scientific, educational, government circles, as well as among representatives of the clergy. The religious component in secular education will give importance to folk culture and traditional religion, which will form concepts such as tolerance and respect for other faiths and cultures, which is important in the context of globalization of the world.